Effects of Calcination Time on Structure and Activity of Porous TiO2-Al2O3 Photocatalyst - Zhang, Wenjie; Xin, Hongliang; Li, Ruyuan; He, Hongbo (Asian Journal of Chemistry, 2013)
A novel porous TiO2-Al2O3 composite nano-material was prepared by sol-gel preparation method. The materials prepared after different calcination times were all composed of anatase TiO2 and amorphous Al2O3. Crystallite sizes of anatase TiO2 were 10.06, 10.55 and 11.13 nm for the samples calcinated for 1, 2 and 3 h, respectively. The surfaces of the materials were very rough with long grooves on the surface. BET specific area, pore volume and average pore size of the materials varied with calcination time. The sample calcinated for 2.5 h had the maximum specific area of 128.9 m2 g-1. The sample calcinated for 3 h showed the maximum photocatalytic activity and adsorption capacity. The average pore size for the material was 14.56 nm and the total pore volume was 0.3945 cm3 g-1 for the sample calcinated for 3 h. After 90 min of reaction, degradation rate of methyl orange on the material was 77.0 % and the total dye decoloration rate was 95.1 %.